Evaluation of POST-Harvest Herbicide Applications for Seed Prevention of Glyphosate-Resistant Palmer amaranth (Amaranthus palmeri) - Crow, Whitney D; Steckel, Lawrence E; Hayes, Robert M; Mueller, Thomas C (Weed technology, 2015)
Recent increases in the prevalence of glyphosate-resistant (GR) Palmer amaranth mandate that new control strategies be developed to optimize weed control and crop performance. A field study was conducted in 2012 and 2013 in Jackson, TN, and in 2013 in Knoxville, TN, to evaluate POST weed management programs applied after harvest (POST-harvest) for prevention of seed production from GR Palmer amaranth and to evaluate herbicide carryover to winter wheat. Treatments were applied POST-harvest to corn stubble, with three applications followed by a PRE herbicide applied at wheat planting. Paraquat alone or mixed with S-metolachlor controlled 91% of existing Palmer amaranth 14 d after treatment but did not control regrowth. Paraquat tank-mixed with a residual herbicide of metribuzin, pyroxasulfone, saflufenacil, flumioxazin, pyroxasulfone plus flumioxazin, or pyroxasulfone plus fluthiacet improved control of regrowth or new emergence compared with paraquat alone. All residual herbicide treatments provided similar GR Palmer amaranth control. Through implementation of POST-harvest herbicide applications, the addition of 1,200 seed m−2 or approximately 12 million seed ha−1 to the soil seedbank was prevented. Overall, the addition of a residual herbicide provided only 4 to 7% more GR Palmer amaranth control than paraquat alone. Wheat injury was evident (< 10%) in 2012 from the PRE applications, but not in 2013. Wheat grain yield was not adversely affected by any herbicide application. Nomenclature: Pyroxasulfone, 5-(difluoromethoxy)-1-methyl-3-(trifluoromethyl)pyrazol-4-ylmethyl 4,5-dihydro-5,5-dimethyl-1,2-oxazol-3-yl sulfone; Palmer amaranth, Amaranthus palmeri S. Wats; corn, Zea mays L.; wheat, Triticum aestivum L. Aumentos recientes en la prevalencia de Amaranthus palmeri resistente a glyphosate (GR) requiere que nuevas estrategias de control sean desarrolladas para optimizar el control de malezas y el desempeño de los cultivos. Se realizó un estudio de campo en 2012 y 2013, en Jackson, Tennessee, y en 2013 en Knoxville, Tennessee, para evaluar programas de manejo de malezas POST aplicados después de la cosecha (POST-cosecha) para la prevención de la producción de semilla de A. palmeri GR y para evaluar la residualidad de los herbicidas durante el trigo de invierno. Los tratamientos fueron aplicados POST-cosecha a campos después de la cosecha del maíz, con tres aplicaciones seguidas por un herbicida PRE aplicado al momento de la siembra del trigo. Paraquat solo o en mezcla con S-metolachlor controló 91% del A. palmeri existente 14 d después del tratamiento, pero no controló el rebrote de la maleza. La mezcla en tanque de paraquat con un herbicida residual ya sea metribuzin, pyroxasulfone, saflufenacil, flumioxazin, pyroxasulfone más flumioxazin, o pyroxasulfone más fluthiacet mejoró el control de rebrotes o nueva emergencia de plántulas al compararse con paraquat solo. Mediante la implementación de aplicaciones de herbicidas POST-cosecha se previno la adición al banco de semillas de 1,200 semillas m−2 o aproximadamente 12 millones de semillas ha−1. En general, la adición de un herbicida residual brindó solamente 4 a 7% más control de A. palmeri GR que paraquat solo. El daño al trigo fue vidente (<10%) con las aplicaciones PRE en 2012, pero no en 2013. El rendimiento de grano del trigo no fue afectado adversamente por ninguna de las aplicaciones de herbicidas.